Enhancement of heat transfer in heat sink under the effect of a magnetic field and an impingement jet - Azadi, Shervin; Abjadi, Ali; Vahdat Azad, Abazar; Ahmadi Danesh Ashtiani, Hossein; Afshar, Hossein (Frontiers in Mechanical Engineering, 2023)
Improving the performance of heat sinks is very important in the development of cooling systems. In this study, the use of a novel combination method (magnetic field impingement jet (MF-IJ)) to improve the convective heat transfer coefficient in a designed heat sink is numerically investigated. To model heat transfer, a steady three-dimensional computational fluid dynamics (CFD) approach is employed. Numerical results including velocity and temperature contours, as well as the distribution of wall temperature of the heat sink and also the convective heat transfer coefficient are analyzed. The results show that the use of ferrofluid (Fe3O4/water) flow with an external magnetic field alone increases the heat transfer coefficient by 10%, while the use of an air impingement jet with pure water and without a magnetic field increases it by 22.4%. By using the MF-IJ method, a 32% enhancement of heat transfer coefficient is achieved compared to the case of pure water flow and without MF-IJ. Based on results, at a Reynolds number of 600, by applying the magnetic field intensities of 400, 800, and 1600 G, the average heat transfer coefficient increases by 5.35, 11.77, and 16.11 %, respectively. It is also found that the cooling of the heat sink and temperature distribution is improved by increasing the Reynolds number and the inlet mass flow rate of the impingement jet. For instance, at z = 0.02 m, the application of an impingement jet with mass flow rates of 0.001, 0.004, and 0.005 kg/s results in a respective increase of 0.36, 1.62, and 1.82% in wall temperature. The results of the current study suggest that the combination method of MF-IJ can be utilized for heat sinks with high heat flux generation as a flow control device.